An Analysis of Cooperative Maxim Used by Indonesia’s President Candidates in Presidential Debate 2024 - Purnama Sari, Dian (BiCED Proceeding, 2024)
This study aimed at analyzing the cooperative maxim used by three Indonesian president candidates of 2024. More specifically, the goal of this study is to recognize the types of cooperative maxim used by Anis Baswedan, Prabowo Subianto, and Ganjar Pranowo during presidential debate 2024. Grice’s cooperative maxim was used to examine four types of maxims. The researchers employed a qualitative descriptive method that the data were collected from the candidates’ utterances during the debate session. The results of this research showed that all four types of cooperative maxims were found (quantity, quality, relation and manner) 70 times. The most common maxim found was maxim of quantity and quality with 18 times occurance per each maxim. Meanwhile, the least common was disgrading maxim of manner and relation with 17 times occurance per each maxim.